Uma contribuição à contabilização de Swap cambial como instrumento de Hedge para empresas não financeiras: Hedge Accounting - Payan, Pedro Carlos (2009)
Companies can use derivative instruments for covering risks. With the use of these instruments the problems appear in the measurement, accounting, and the disclosures. This project s objective based on a case study is to analyze the Derivative Instrument (Foreign Exchange Swap) as the countable theory and international norms of the FASB, IASB and Brazilian Norms. The Brazilian Norms are published by the CPC and together these norms are the make up of the CVM. This case study demonstrated the process of the operation, the criteria for the measurement, as well as the accounting aspect. The reasons behind this project are first, the significant volume in the transactions of Swap at the end of 2008, which reached R$ 12,6 billion. Second the risk involving these operations, the difficulty encountered by accounting for the recognition, measurement and disclosure. The collected data applied from the systems of calculations and evaluations of the instruments are then compared to the collected data reported by the company. There are no significant differences in these calculations except having discrepancy in the use of accounts, which results in the registration in Swap Accounting. Three situations dealing with assets were compared by the Derivatives Instrument: a) traditionally for the curve of the paper: the financial accounts and results of the period are affected; b) recording the marking to market without hedge accounting: it showed different balances in the item accounts; c) recording the marking to market with hedge accounting: there were alterations in the result of the period, in the financial accounts and in the total shareholder s equity